Annals of the caliphs' kitchens : Ibn Sayyār al-Warrāq's tenth-century Baghdadi cookbook - Ibn Sayyār al-Warrāq, al-Muẓaffar ibn Naṣr, 10th cent.? (Islamic History and Civilization, 2007)
Written nearly a thousand years ago, al-Warraq's cookbook is the most comprehensive work of its kind. This traditional cookbook with more than 600 recipes from the luxurious cuisine of medieval Islam is also a rare guide to the contemporary culinary culture. Its numerous anecdotes and poems unfold the role of food in the politics of Islam's golden era. Introducing this elegant translation is a thorough survey of the period and its food culture. An extensive Glossary, in Arabic and English, of medieval ingredients and dishes, and an Appendix of historical figures provide the necessary reference tools for this work. Making this key resource available in English for the first time to scholars and the general reader fills a gap in the cultural history of medieval Islam. Over 30 color illustrations.